Recent synthesis of thietanes - Xu, Jiaxi (Beilstein Journal of Organic Chemistry, 2020)
Thietanes are important aliphatic four-membered thiaheterocycles that are found in the pharmaceutical core and structural motifs of some biological compounds. They are also useful intermediates in organic synthesis. Various synthetic methods of thietanes have been developed, including inter- and intramolecular nucleophilic thioetherifications, photochemical [2 + 2] cycloadditions, ring expansions and contractions, nucleophilic cyclizations, and some miscellaneous methods. The recently developed methods provide some new strategies for the efficient preparation of thietanes and their derivatives. This review focuses on the synthetic methods to construct thietane backbones developed during 1966 to 2019.
Keywords: cycloaddition; cyclization; ring contraction; ring expansion; thietane; thiotherification